PEMENUHAN HAK KHUSUS BAGI NARAPIDANA PEREMPUAN HAMIL YANG MENJALANI MASA TUNGGU HUKUMAN MATI DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Dwi Indrawan Mustapa; Sunardi Purwanda; Auliah Ambarwati (Jurnal Ilmiah Dinamika Hukum, 2023)
This research was conducted with the aim of finding out the arrangements for the death penalty for climbing pregnant women and knowing the legal reasons for having to fulfill special rights, for example pregnancy, childbirth and breastfeeding for female prisoners who are temporarily carrying out the waiting period for execution of the death penalty. The type of research used in this research is normative research. Normative legal research is more likely to describe law as a descriptive discipline. Law Number 1 of 2023 which has been passed as a new law provides information that the implementation of the death penalty refers to Article 98 of Law Number 1 of 2023 which stipulates that capital punishment is punishable by an alternative which is only permitted to be released after a request for clemency for convicts who are rejected by the President. However, for pregnant women, women who are breastfeeding their babies, it turns out that it can be postponed until the women give birth, the women no longer breastfeed their babies, and also get a 10-year probation period for convicts to do good in prison. So there is a period of 10 years for the pregnant woman's desire to do good while being detained in prison.